Comparison of the performance of PV and PV/T systems through computational modeling applied to a commercial consumer unit - Fiorotti, Rodrigo; Bermudes Prati Sant'Ana, Brunella; de Oliveira Rocha, Helder Roberto; Farias Fardin, Jussara; Coutinho, Carlos Roberto (Latin American Journal of Energy Research, 2025)
This work presents a comparative case study, through computational simulations using Matlab software, between the installation of a conventional PV system and a hybrid PV/T system in a hotel located in Vila Velha–ES, where water heating for 45 suites is carried out by electric showers. The simulations considered meteorological data (solar irradiance and ambient temperature), an electrical consumption profile obtained through measurement, as well as installation constraints related to available area and shading. The results indicated that, although the PV/T system has a lower peak power and occupies a smaller area, it demonstrates superior performance when considering the total energy balance. The main advantage observed was a 12.07% reduction in total load consumption, resulting from the use of thermal energy for water heating, which reduces electrical demand. This substitution led to a decrease in grid consumption and an increase of 284.5% in the financial credit generated at the end of the simulated period. The findings demonstrate that the PV/T system represents a more efficient solution for facilities with high water heating demand, optimizing space utilization and contributing to the reduction of electrical grid load. Keywords: Hybrid Photovoltaic/Thermal System; Photovoltaic System; Energy Efficiency; Water Heating; Computational Simulation.